Relay transport of aerosols to Beijing-Tianjin-Hebei region by multi-scale atmospheric circulations. (September 2017) - Miao, Yucong; Guo, Jianping; Liu, Shuhua; Liu, Huan; Zhang, Gen; Yan, Yan; He, Jing
Abstract: The Beijing-Tianjin-Hebei (BTH) region experiences heavy aerosol pollution, which is found to have close relationships with the synoptic- and local-scale atmospheric circulations. However, how and to what extent these multi-scale circulations interplay to modulate aerosol transport have not been fully understood. To this end, this study comprehensively investigated the impacts of these circulations on aerosol transport in BTH by focusing on an episode occurred on 1 June 2013 through combining both observations and three-dimensional simulations. It was found that during this episode, the Bohai Sea acted as a transfer station, and the high-pressure system over the Yellow Sea and sea-breeze in BTH took turns to affect the transport of aerosols. In the morning, influenced by the high-pressure system, lots of aerosols emitted from Shandong and Jiangsu provinces were first transported to the Bohai Sea. After then, these aerosols were brought to the BTH region in the afternoon through the inland penetration of sea-breeze, significantly exacerbating the air quality in BTH. The inland penetration of sea-breeze could be identified by the sharp changes in ground-based observed temperature, humidity, and wind when the sea-breeze front (SBF) passed by. Combining observations with model outputs, the SBF was found to be able to advance inland more than ∼150 km till reaching Beijing. This study has important implications for better understanding the aerosol transport in BTH, and improving the forecast of such aerosol pollution. Highlights: Penetration of sea-breeze to Beijing was identified by observations. Synergistic effects of multi-scale circulations on aerosol pollutant transport were revealed. Both observations and modeling well reproduce the relay transport processes of aerosols.